2022
DOI: 10.1111/acel.13627
|View full text |Cite
|
Sign up to set email alerts
|

Can mild cognitive impairment and Alzheimer’s disease be diagnosed by monitoring a miRNA triad in the blood?

Abstract: Aging is coupled with a progressive decline in cognitive abilities in a significant percentage of individuals. Such age-related cognitive impairment (ACI) is characterized by declines in the overall gray matter and hippocampus volumes (Harada et al., 2013;Sanford, 2017), with some changes commencing at ~20 years of age (Terry & Katzman, 2001). Many factors increase ACI risk, including neuroinflammation, diabetes, depression, hypothyroidism, number of surgeries, and can-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Similarly, some studies indicated that miR-146a-5p was specific to microglia or mainly derived from microglia, and the deletion of miR-146a could affect function and proteome of microglia [ 50 , 51 ]. We know that miR-146a-5p is an inflammation-related miRNA, which plays an indispensable role in regulating the pathology of AD and the development of depression [ 27 , 52 , 53 ]. However, other studies have indicated that miRNA overexpression does not seem to induce cognitive deficits in wild mice [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some studies indicated that miR-146a-5p was specific to microglia or mainly derived from microglia, and the deletion of miR-146a could affect function and proteome of microglia [ 50 , 51 ]. We know that miR-146a-5p is an inflammation-related miRNA, which plays an indispensable role in regulating the pathology of AD and the development of depression [ 27 , 52 , 53 ]. However, other studies have indicated that miRNA overexpression does not seem to induce cognitive deficits in wild mice [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to this, these patients are more likely to progress and present later with severe forms of cognitive impairment. There is need to support primary healthcare providers in diabetic and hypertensive clinics with mental health training in order to equip them with knowledge and skills to screen and identify dementia in its early stages and initiate the appropriate management strategies and timely referrals to halt and retard progression ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their expression and activity are often dysregulated in pathological states resulting in a shift of the cellular and extracellular miRNA patterns. Therefore, miRNA profiling along with the analysis of their target signaling pathways has emerged as a promising approach to study the pathogenesis of many diseases (Chen et al, 2010;Geekiyanage et al, 2012;Bencurova et al, 2017;Paul et al, 2018;Figueiredo et al, 2022;Khan and Saraya, 2022;Wei and Shetty, 2022).…”
Section: Introductionmentioning
confidence: 99%